2021
DOI: 10.3390/cancers13215450
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Extracellular Vesicles in Gastrointestinal Tract Cancer: An Unexplored Territory

Abstract: Bacterial extracellular vesicles are membrane-enclosed, lipid bi-layer nanostructures that carry different classes of biomolecules, such as nucleic acids, lipids, proteins, and diverse types of small molecular metabolites, as their cargo. Almost all of the bacteria in the gut secrete extracellular vesicles to assist them in competition, survival, material exchange, host immune modulation, infection, and invasion. The role of gut microbiota in the development, progression, and pathogenesis of gastrointestinal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 282 publications
(379 reference statements)
0
18
0
Order By: Relevance
“…After SCS treatment (High group), the relative abundance of Fusobacteria decreased by ~100-fold. Fusobacteria are common human pathogens, can participate in a variety of infections, such as appendicitis and inflammatory bowel disease [ 26 , 27 ]. Recent studies found Fusobacteria can promote colon tumor formation in animal models, and is abnormally enriched in colon cancer patients [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…After SCS treatment (High group), the relative abundance of Fusobacteria decreased by ~100-fold. Fusobacteria are common human pathogens, can participate in a variety of infections, such as appendicitis and inflammatory bowel disease [ 26 , 27 ]. Recent studies found Fusobacteria can promote colon tumor formation in animal models, and is abnormally enriched in colon cancer patients [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The nanosized and non-replicative status of bEVs, their ability to be bioengineered to produce desired effect [ 106 , 107 ], their accumulation near the tumor sites, their capacity to induce anti-tumor immune responses [ 15 , 108 ], and their ability to carry the desired payloads [ 109 , 110 ] provide lucrative incentives for the further study of bEVs in order to fill the current knowledge gap as well as to develop optimized novel cancer therapy modules ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The systematically released bEVs could then trigger tolerogenic immune reprogramming of the TME, thereby acting as tumor-promoting entities, and could also traverse to distant tissues and organs [ 14 ]. In contrast, bEVs derived from certain gram-negative bacteria such as Vibrio cholera , Escherichia coli (BL21), and Shigella flexneri have been found to significantly inhibit tumor growth when injected into colon tumor-bearing mice [ 15 ]. Consequently, bEVs present a promising prospect for further comprehending carcinogenesis and disease progression, improving existing immunotherapies, and formulating new targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
“… 22 As it aids in our understanding of molecular mechanism diversity, metabolomics can also be applied to precision medicine to improve human health, such as for metabolic and cardiac diseases, cancer, longevity, and nervous system diseases. 23 , 24 Additionally, due to the interference of environmental enzymes, initial genomics and transcriptomics are not completely linear with the downstream metabolites, as side reactions may simultaneously happen, resulting in unexpected products. 25 It is thus not enough to concentrate solely on the genomics and transcriptomics, as the whole molecular landscape should be understood.…”
Section: Introductionmentioning
confidence: 99%